EFFECTIVENESS OF EDUCATION ON REPRODUCTIVE HEALTH IN IMPROVING KNOWLEDGE AND ATTITUDES TOWARD CHILD MARRIAGE PREVENTION AT THE ADOLESCENT POSYANDU IN TRUCUK - Vera farida; Lisviarose; Dilgu Mery; Hirza Rahmita (PT. Radja Intercontinental Publishing, 2026)
Family planning coverage at the Sadar Jaya Community Health Center in Siak Kecil Subdistrict, Bengkalis Regency, showed that out of 353 pregnant women, only 1 was an IUD user (IUD contraceptive use remained low compared to other non-MKJP contraceptives). This study aimed to examine the effect of counseling using leaflets on improving postpartum IUD family planning knowledge among third-trimester pregnant women. This was a pre-experimental study. The population comprised of all third-trimester pregnant women in May 2026, totaling 45 individuals; total sampling was used. Data analysis used the t-test. The results showed that prior to the education session, the majority (57.2%) of participants had adequate knowledge of postpartum IUD contraception. After the education session, the majority (66.7%) had good knowledge of postpartum IUD contraception. The effect of education using leaflets on the improvement of postpartum IUD knowledge among third-trimester pregnant women had a p-value of 0.000 < 0.05. The conclusion of this study is that health education using leaflets has an effect on increasing knowledge of postpartum IUD family planning among pregnant women in their third trimester. Therefore, improve their knowledge and understanding, particularly in providing services to pregnant women, regarding postpartum IUD family planning for pregnant women in their third trimester.